The Influence of Learning Discipline and Family Environment on Learning Outcomes in Economics Subjects - Arifin, Khairul; Putra, Andi Riswandi Buana; Nurrohman, Heru; Supriyadi, Arif; Sabela, Windari (International Journal of Universal Education, 2023)
Background: the learning outcomes of students have not met the Minimum Completeness Criteria 73 set by the school. This can be seen from the average score of students in the form of Mid Semester Tests from economic subjects of 58.54 or an average completeness of 31% of 164 students consisting of 114 students who have not completed the class. Aim: This study aims to determine the effect of learning discipline on the environment and family on the learning outcomes of economic subjects of students in class XI IPS Senior High School 4 Palangkaraya. Method: This research includes quantitative research, the population in this study were all students of class XI IPS Senior High School 4 Palangkaraya totalling 164 students with a sample representing the entire population of 116 students. Data collection is done by questionnaire method. Data analysis techniques using cycles: normality test, linearity test, multicollinearity test, multiple linear regression test and hypothesis testing. Results and Dıscussion: The results showed that: (1) there is an effect of learning discipline in economic subjects of students in class IX IPS obtained a significance level of 0.000 <0.05, then learning discipline is declared to have an effect on learning outcomes of 22.2%, obtained from the results of the coefficient of partial determination. (2) there is an influence of the family environment of economic subjects for students in class IX IPS obtained a significance level of 0.000 <0.05, then learning discipline is declared to have an effect on learning outcomes by 25.3%, obtained from the results of the partial determination coefficient. (3) there is an influence of learning discipline and family environment on the economic subjects of class IX social studies students obtained a significance level of 0.000 <0.05, then learning discipline and family environment are declared to have an effect on learning outcomes by 47.5%, obtained from the results of the coefficient of determination.